2021
DOI: 10.33609/2708-129x.87.01.2021.23-40
|View full text |Cite
|
Sign up to set email alerts
|

ISOTHERMAL SECTION STRUCTURE THE ZrO2-La2O3-Gd2O3 SYSTEM AT 1500 °С

Abstract: Using the methods of physicochemical analysis (XRD, petrography, scanning electron microscopy analyses) phase equilibria were firstly investigated in the ternary system ZrO2–La2O3–Gd2O3 system at 1500 ºС. It was established that in the system there exist fields of solid solutions based on hexagonal (A) modification of La2O3 and cubic with fluorite-type structure (F) and tetragonal (Т) modification ZrО2 , cubic (С) and monoclinic (M) modification Gd2O3 and ordered intermediate phase with pyrochlore-type structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…The concentration boundary of the region of homogeneity of these solid solutions is curved in the direction of decreasing cerium dioxide content and extends from the corresponding coordinates in the limiting binary systems CeO2-La2O3 (100-49 mol % La2O3) and CeO2-Yb2O3 (100-26 mol% Yb2O3). Using the literature data [29][30][31][32], it was found that in this system the region of homogeneity of these solid solutions slightly increases in comparison with other systems of the series CeO2-La2O3-Ln2O3 (Ln = Sm, Eu, Gd).…”
Section: Figmentioning
confidence: 84%
See 1 more Smart Citation
“…The concentration boundary of the region of homogeneity of these solid solutions is curved in the direction of decreasing cerium dioxide content and extends from the corresponding coordinates in the limiting binary systems CeO2-La2O3 (100-49 mol % La2O3) and CeO2-Yb2O3 (100-26 mol% Yb2O3). Using the literature data [29][30][31][32], it was found that in this system the region of homogeneity of these solid solutions slightly increases in comparison with other systems of the series CeO2-La2O3-Ln2O3 (Ln = Sm, Eu, Gd).…”
Section: Figmentioning
confidence: 84%
“…9. h. Using data [29][30][31][32], it was found that this region of homogeneity significantly decreases with decreasing ionic radius of lanthanide. In [32] it was indicated that the maximum solubility of CeO2 in a cubic solid solution based on C-Er2O3 is 20 mol%.…”
mentioning
confidence: 99%
“…The phase relations and structure of the phases formed in the La2O3-Gd2O3 system were studied in [22][23][24][25][26][27][28][29][30][31]. Graphic interpretation of the obtained data is shown in Figure 1.…”
Section: Introductionmentioning
confidence: 99%